Vieillissement en bonne santé dans l'Inuit Nunangat : vers un modèle géographique des déterminants sociaux de la santé - Baron, Marie (Université Laval, 2019)
Background: The aging of the Inuit population is a new phenomenon creating new and unique social and health challenges across the Arctic. There is relatively limited evidence about the health profile and the social determinants of health (SDH) for Inuit elders. The definition of Inuit health is holistic, and is anchored in a geographical dimension such that health is created through interactions between people and the land. This geographic dimension is central to understand the role of SDH in supporting healthy aging, yet are seldom included in Inuit SDH models. The overall aim of my doctoral thesis is to conceptualize and operationalize a model of the sociogeographic determinants supporting healthy aging in Inuit communities. This model is built in coherence with Inuit’s definition of health which is The thesis follows three research objectives: 1) to conceptualize, operationalize and validate the concept of health for older Inuit aged 50 years and over; 2) to identify social determinants of health (SDH) at the individual, housing, and community levels associated with healthy aging; and 3) to explore the geographical dimension of the mechanisms connecting the social determinants to healthy aging. Methods: This thesis employs a mixed-methods exploratory and explanatory research design. Qualitative data used to conceptualize the definition of health for Inuit elders were retrieved from workshops conducted in two Nunavik communities in 2016. Using quantitative data from the 2006 Aboriginal Peoples Survey (APS) (n = 850 Inuit ≥ 50 years), latent class analyses was then used to operationalize the definition of health into a holistic indicator health. Associations between this indicator and selected SDH at the individual, housing and community scales were modelled using multinomial regressions. To further explore the geographical dimension of the SDH, and to understand the mechanisms linking the SDH to health, in-depth interviews and one focus groups with 20 participants aged 50 to 86 were conducted in Baker Lake, ...